A clinical study to assess the patterns of muco-cutaneous changes in newborns during the first five days after birth - Kurian, Anu; Patidar, Ritesh; Kumar, G V; Narendra, G (Indian Journal of Child Health, 2018)
Background: Skin is the largest organ in the human body accounting for approximately 13% of the neonatal body weight as compared to 3% of the adult weight. It is the most visible and easily accessible organ of the body. Objective: To study the patterns of muco-cutaneous changes in newborns during the first 5 days after birth. Materials and Methods: This prospective study was conducted in postnatal wards of department of Obstetrics and gynaecology and neonatal unit of department of Paediatrics of a tertiary care teaching hospital. All the newborns within first 5 days after birth, irrespective of gender, underlying disease and general condition of the baby were included in the study. All the newborns were examined within 24 h of birth and followed up till 4 days after birth and the findings were noted in the preformed case-study proforma. Results: The present study was conducted on 200 newborns with cutaneous lesions. The muco-cutaneous diseases were divided into physiological, transient and pathological diseases. Among these newborns 114 (57%) were males, and 86 (43%) were females. The most common manifestations observed were Mongolian spots 156 (78%), sebaceous gland hyperplasia 81 (40.5%), Epstein pearls 79 (39.5%), milia 43 (21.5%), physiological jaundice 16 (8%), vernix caseosa 14 (7%), erythema toxicum 13(6.5%), salmon patch 5 (2.5%), hypertrichosis/lanugo 2 (1%), sucking blisters 1 (0.5%) and bacterial infection of Staphylococcal scalded skin syndrome 1 (0.5%). Conclusion: Muco-cutaneous manifestations are very common in neonates but as these are the transient conditions, so no intervention is required. Early recognition of these lesions is important to distinguish them from more serious skin disorders.